2020
DOI: 10.1111/1751-2980.12958
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of gastric antral vascular ectasia in real‐life settings: Argon plasma coagulation or endoscopic band ligation?

Abstract: ObjectiveThe efficacy of argon plasma coagulation (APC) on gastric antral vascular ectasia (GAVE) may be impaired over time and depends greatly on the application settings. Endoscopic band ligation (EBL) may be an alternative, but study on its efficacy is limited. This study aimed to evaluate and compare the clinical efficacy of APC and EBL in treating GAVE.MethodsChanges in the need for blood transfusion, number of treatment sessions and hospitalizations were retrospectively assessed in 63 transfusion‐depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The transfusion-dependent rate after APC is 9.1–50% 21 23 , 25 , 30 32 [ Figure 2(b) ]. The causes of transfusion after APC are often varied.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
See 4 more Smart Citations
“…The transfusion-dependent rate after APC is 9.1–50% 21 23 , 25 , 30 32 [ Figure 2(b) ]. The causes of transfusion after APC are often varied.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
“…Hyperplastic gastric polyps 25 , 35 , 37 and fever 40 after APC have also been reported. Major adverse events are uncommon, including Mallory–Weiss syndrome, 32 scarring of ulcer, 22 , 32 and sepsis. 21 , 35 Probst et al 22 reported that one patient developed deep antrum ulcers followed by circumferential scarring of the antrum and asymptomatic stenosis 6 months after APC, and planned to undergo Billroth I surgery.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
See 3 more Smart Citations